Intimately forsaken a Trinitarian Christology of the cross - Brand, Thomas (Palgrave Macmillan, 2024)
Zusammenfassung: This book approaches one of the most complex of theological problems – the seeming distance between the Father who sends the Son and the Son who dies on the cross. Brand gives us a rich and stimulating exposition bursting with careful historical investigation and philosophical rigour that is worth the attention of us all.’ - Lewis Ayres, Professor of Catholic and Historical Theology, Durham University. Brand has admirably and fearlessly addressed this issue, and he has done so in a thoroughly well researched and scholarly manner. He tackles all the biblical and theological issues concerning divine impassibility and the communication of idioms in a clear, creative, and insightful manner. A must read for those struggling to comprehend this marvellous mystery of faith. - Thomas G.
Keywords: Theology.; Theologia crucis; Trinitätslehre; Christian Theology.; Hochschulschrift